1997
DOI: 10.1254/jjp.73.337
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of Lisinopril on Puromycin Aminonucleoside Nephrosis in Unilaterally Nephrectomized Rats.

Abstract: ABSTRACT-The therapeutic effects of angiotensin converting enzyme inhibitor, lisinopril, on puromycin aminonucleoside (PAN)-induced nephrosis were investigated using unilaterally nephrectomized rats. Lisinopril showed potent dual effects on PAN nephrosis. Lisinopril treatment (50 mg/l in drinking water) from day 5 or day 9 reduced urinary protein excretion and suppressed the development of glomerular sclerosis at 8 weeks after PAN injection (150 mg/kg, i.p.), indicating a therapeutic effect on the nephrosis. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Our impression is that the pathomechanisms involved in early PAN may be beyond the reach of being significantly affected by ACE inhibitors. Earlier studies show variable results [36,37,38,39]. Recent studies separating the two types of angiotensin receptors have suggested that they have opposite actions [40].…”
Section: Discussionmentioning
confidence: 99%
“…Our impression is that the pathomechanisms involved in early PAN may be beyond the reach of being significantly affected by ACE inhibitors. Earlier studies show variable results [36,37,38,39]. Recent studies separating the two types of angiotensin receptors have suggested that they have opposite actions [40].…”
Section: Discussionmentioning
confidence: 99%
“…Lisinopril 20 mg/kg has anti-hypertensive effect in previous pre-clinical studies, whereas lisinopril 50 mg/kg reduced urinary protein excretion, indicating therapeutic action of lisinopril against proteinuria. [151617] Rosuvastatin 40 mg/kg showed anti-hyperlipidemic effect in previous studies, whereas higher dose (≥80 mg/kg) of rosuvastatin induced myopathy in rats. [1819]…”
Section: Methodsmentioning
confidence: 99%
“…The detection of ACSs on the GBM was performed as previously reported [29]. The kidney was cut into small pieces and immersed in a mixture of 0.1% glutaraldehyde and 2% phosphotungstic acid.…”
Section: Methodsmentioning
confidence: 99%